Free Software, Business Capital, and Institutional Change: A Veblenian Analysis of the Software Industry. - Kologlugil, Serhat (Journal of Economic Issues, 2012)
Free software, unlike proprietary software under exclusive copyright control, exemplifies a form of productive and innovative activity that is based upon mutual sharing of technological knowledge. Free software engineers, who get connected through various software-development projects, voluntarily contribute their time and skills to produce computer programs which, they insist, should be free for anyone to use, modify, and distribute. This paper argues that Thorstein Veblen's socio-economic theory - in particular his conceptions of capital, technological knowledge and institutional change - offers a fruitful framework to analyze the emergence of free software as an economic and social phenomenon. From the Veblenian perspective, the free software movement argues that the technological knowledge in the software industry should freely be available to society as a part of its common stock of knowledge. In other words, they are against the use of copyright law as a predatory strategy by software corporations, while the current technological conditions in the software industry allow for an institutional arrangement of production and innovation based on cooperative habits of thought.